Effect of early pregnancy on the expression of progesterone receptor and progesterone-induced blocking factor 1 in ovine liver - Leying Zhang; Chen Zhuang; Zimo Zhao; Ning Li; Jiachen Bai; Ling Yang (Czech Journal of Animal Science, 2019)
Liver plays important roles in the innate and adaptive immunity, and contributes to the maternal immune adjustments during pregnancy. Progesterone (P4) has key effects on immunomodulation of the maternal uterus during pregnancy. In this study, livers were obtained at day 16 of the estrous cycle and at days 13, 16 and 25 of pregnancy (n = 6 for each group) in ewes. The effects of early pregnancy on the expression of P4 receptor (PGR) and progesterone-induced blocking factor 1 (PIBF1) were analysed through RT-qPCR assay, Western blot and immunohistochemistry analysis. Our results showed that the isoforms of PGR with molecular weights of approximately 60 kDa (PGR60) and 89 kDa (PGR89) were strongly expressed in the livers from pregnant ewes (P < 0.05), but there was no expression of the isoform of PIBF1 with a molecular weight of approximately 55 kDa (PIBF55) on day 13 of pregnancy. The PGR protein was mainly limited to the endothelial cells of the proper hepatic arteries and portal veins, and hepatic cells. In conclusion, the PGR89 and PGR60 were up-regulated, and PIBF55 was down-regulated on day 13 of pregnancy, which may be involved in maternal hepatic immunoregulation during early pregnancy in sheep.